2018
DOI: 10.1016/j.ultsonch.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vibration duration of high ultrasound applied to bio-composite while gelatinized on its properties

Abstract: A B S T R A C TThis article reports effect of vibration duration of high ultrasound applied to bio-composite while gelatinized on its properties. The bio-composite consists of mixing of both the tapioca starch based bioplastic and oil palm empty fruit bunch (OPEFB) fibers with high volume fraction. Gelatinization of the bio-composite sample was poured into a rectangular glass mold placed then in an ultrasonic bath with 40 kHz, and 250 watt in different duration for 0, 15, 30, 60 min respectively. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 27 publications
5
33
0
5
Order By: Relevance
“…These include water hyacinth [10][11][12], oil palm empty fruit bunch (OPEFB) [13], banana (pseudo stem), jute (stem) and pineapple leaf fiber [2], arecanut husk fiber [14], kenaf bast (Hibiscus cannabinus) [15], coconut husk [16], Helicteres isora plant [17] and bacterial cellulose [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These include water hyacinth [10][11][12], oil palm empty fruit bunch (OPEFB) [13], banana (pseudo stem), jute (stem) and pineapple leaf fiber [2], arecanut husk fiber [14], kenaf bast (Hibiscus cannabinus) [15], coconut husk [16], Helicteres isora plant [17] and bacterial cellulose [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Brittleness has been reduced by mixing in a plasticizer such as glycerol . To increase tensile strength and water resistance, fillers obtained from natural fibers have been added to starch‐based biopolymers to produce biocomposites . Chen et al reported an improvement of mechanical properties, thermal, and moisture resistance of biocomposites that included cellulose nanoparticles from natural sources.…”
Section: Introductionmentioning
confidence: 99%
“…This method is similar to the one reported in more detail in a previous study . TGA and DTG of samples were measured using a thermal analysis instrument (TGA Q500 V20.6, USA).…”
Section: Materials and Experimentsmentioning
confidence: 97%
“…A similar method was used to the one reported in more detail in a previous study . PANalyticalXpert PRO at 25 °C, 40 kV, and 30 mA was used to perform X‐ray diffraction testing.…”
Section: Materials and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation